Critical Insights into the Impact of Artificial Intelligence on Mental Health, Patient Rights, and Human Rights - Sangramjeet Chavan; Vojjala Sahiti; Shashikala Gurpur; Atmaram Shelke (Australasian Accounting, Business and Finance Journal, 2025)
Artificial Intelligence (AI) technologies are changing many aspects of contemporary life, including the emergence of mental healthcare as a field for innovation. This interdisciplinary research investigates the complex interactions between Artificial Intelligence, Mental Health Care, Patient Rights, and Human Rights to assess the advantages and disadvantages of incorporating AI into Mental Health Services. Globally, millions of people suffer from mental disorders, placing significant strains on health systems and societies. Mental health care has always been restricted due to stigma, structural barriers and lack of resources, often leading to an inability to provide accessible and effective treatments despite increasing patient demands. AI technology has emerged as a possible solution for age-old issues like efficient early detection methods, treatment strategies, and personal follow-up. Conversely, AI application in this delicate area raises ethical and legal dilemmas about people’s freedoms, which must be assessed critically, and predictable steps must be taken to protect patient rights.
Keywords: Artificial Intelligence; Mental Health; Patient Rights; Human Rights; Healthcare Ethics